Impacto de la Ley de Minería en la minería artesanal y pequeña minería en la Parroquia 28 de Mayo del cantón Yacuambi, Provincia de Zamora Chinchipe - Malo Robles, María Daniela (2014)
This research refers to the Mining Act and its impact on the people of the Parish "28 de Mayo", canton of Yacuambi, located in the province of Zamora Chinchipe, letting us know the reasons why this rule is violated and what are the different methods for its proper implementation. It also lets us know the artisanal procedures used by miners and small-scale miners for extracting minerals and the impacts they generate on the environment. The lack of enforcement of existing legislation shows the legal reality, regarding non-compliance of these rules and their legal consequences in the territory in which this research has been applied